2012
DOI: 10.2174/1874306401206010054
|View full text |Cite
|
Sign up to set email alerts
|

Precision in Diagnosing and Classifying COPD: Comparison of Historical Height with Current Height and Arm Span to Predict FEV1

Abstract: Background: Measured reductions in lung function, as a result of COPD, use a measured current value and make comparisons to a determined ‘normal’ value arrived at using a regression equation based upon a patients height. Osteoporosis is a recognised co-morbidity in patients with chronic obstructive pulmonary disease (COPD) and may cause excessive height loss resulting in the ‘normal’ values and disease progression being under-estimated.Purpose: The aim of the study was to examine the height variation in a coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“… 9 , 10 A previous longitudinal study suggests that current measured height may underestimate the progression of COPD, and that the use of arm span to determine height will give a more accurate measure of COPD progression. 25 We disagree with this suggestion because arm span length significantly differed from current standing height in our study. Current standing height is one of the standard variables for pulmonary function measurement; therefore, we may not be able to reliably replace standing height with arm span.…”
Section: Discussioncontrasting
confidence: 74%
“… 9 , 10 A previous longitudinal study suggests that current measured height may underestimate the progression of COPD, and that the use of arm span to determine height will give a more accurate measure of COPD progression. 25 We disagree with this suggestion because arm span length significantly differed from current standing height in our study. Current standing height is one of the standard variables for pulmonary function measurement; therefore, we may not be able to reliably replace standing height with arm span.…”
Section: Discussioncontrasting
confidence: 74%
“…We used recollected height, as slight kyphosis and stoop will affect height measurement but will not alter the lung capacity in the thorax, so height recorded at a younger age might be a better estimate for lung function. A follow-up study in COPD recently found that height estimated from arm span was a better measure for lung function prediction [29]. Future studies in the aged may need to measure arm span as a surrogate for true height to see if this better standardises FEV 1 , to improve survival prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Enright (2012) [70] suggests that we should focus on improving the quality of the spirometry tests performed, which is in line with the findings of this review. Several factors may bias the results of the spirometry test, thereby potentially causing misdiagnosis [38,48,73,74,76]. Yet, again, it seems relevant to provide better support for primary care in COPD diagnosis to improve the quality of the spirometry tests and thus limit misdiagnosis (see Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…Also, physiological changes may influence the spirometry test and cause misdiagnosis. The patient's lungs and height change over time, which may lead to an incorrect lung function test, potentially causing misdiagnosis [76,77].…”
Section: Errors Linked To the Spirometry Testmentioning
confidence: 99%